P1316PREDICTORS OF ARTERIO-VENOUS FISTULA FAILURE: A POST-HOC ANALYSIS OF THE FAVOURED STUDY. (6th June 2020) - See, Yong Pey; Viecelli, Andrea; Voss, David; Mori, Trevor; Kerr, Peter; Paul-Brent, Peta-Anne; Cho, Yeoungjee; Johnson, David W; Hawley, Carmel; Pascoe, Elaine M
Abstract: Background and Aims: An autologous arteriovenous fistula (AVF) is the preferred haemodialysis vascular access but successful creation is hampered by high rates of AVF failure. This study aimed to evaluate patient and surgical factors associated with AVF failure to improve vascular access selection and outcomes. Method: This is a post-hoc analysis of all participants of FAVOURED, a multi-centre, double-blind, multinational, randomized placebo-controlled trial evaluating the effect of fish oil and/or aspirin in preventing AVF failure in patients receiving haemodialysis. The primary outcome of AVF failure was a composite of fistula thrombosis and/or abandonment and/or cannulation failure at 12 months post AVF creation and secondary outcomes included individual outcome components. Patient data (demographics, comorbidities, medications and laboratory data) and surgical factors (surgical expertise, anaesthetic, intraoperative heparin use) were examined using multivariable logistic regression analyses to evaluate associations with AVF failure. Results: Of 536 participants, 253 patients (47%) experienced AVF failure during the study period. The mean age was 55 ± 14.4 years, 64% were male, 45% were diabetic and 4% had peripheral vascular disease. Factors associated with AVF failure included female sex (odds ratio [OR] 1.78, 95% confidence interval [CI] 1.20-2.67), lower diastolic blood pressure (DBP; OR for higher DBP 0.98, 95% CI 0.97-0.99), presence of central venous catheter (OR 1.50, 95% CI 1.02-2.20, p=0.04) and aspirin requirement (OR 1.61, 95% CI 1.01-2.57). Conclusion: Female sex, requirement for aspirin therapy, requiring haemodialysis via a central venous catheter and lower diastolic blood pressure were factors associated with higher odds of AVF failure. These associations have potential implications for vascular access planning and warrant further studies.